Inducibility of Atrial Fibrillation and Flutter Following Pulmonary Vein Ablation. (6th February 2013) - LEONG‐SIT, PETER; ROBINSON, MELISSA; ZADO, ERICA S.; CALLANS, DAVID J.; GARCIA, FERMIN; LIN, DAVID; DIXIT, SANJAY; BALA, RUPA; RILEY, MICHAEL P.; HUTCHINSON, MATHEW D.; COOPER, JOSHUA; GERSTENFELD, EDWARD P.; et al.
Arrhythmia Inducibility Post‐AF Ablation: Introduction: Prior reports demonstrate prognostic value in noninducibility of atrial arrhythmias after atrial fibrillation (AF) ablation and suggest their utility in guiding additional ablation lesion sets. The type and mechanism of induced atrial arrhythmias, their relationship to the underlying atrial substrate, and prognostic significance of induced organized atrial arrhythmias are unknown. Methods and Results: One hundred forty‐four patients (30 women; median age 60 years; 54% with paroxysmal AF) undergoing AF ablation (circumferential pulmonary vein isolation and focal ablation of nonvein triggers on isoproterenol) were evaluated prospectively. All underwent a standardized postablation induction protocol from the coronary sinus and right atrium: 15 beat burst pacing at 250 milliseconds and decrementing to 180 milliseconds. Sustained rhythms were defined as greater than 2 minutes Of 144 patients, 55 patients (38.2%) did not have sustained inducible arrhythmias. Fifty‐two (36.1%) had inducible AF and 37 (25.7%) had inducible organized arrhythmias. A logistic regression analysis showed that age (OR 2.10 per decade; P = 0.003) and hypertension (OR 4.15; P = 0.009) were predictive of inducibility. However, inducibility of either AF or organized arrhythmias was not prognostic of clinical recurrence at 1 year postablation (P = 0.65). Furthermore, inducibility of organized arrhythmias did not predict clinical recurrence of an organized arrhythmia. Only LA size (OR 2.18; 95% CI 1.02–4.67; P = 0.04) and persistent AF (OR 2.43; 95% CI 1.09–5.40; P = 0.03) predicted atrial arrhythmia recurrence. Conclusions: Multisite atrial burst pacing post‐AF ablation induced organized rhythms in 25.7% and AF in 36.1% of patients after AF ablation. Hypertension and age predict inducibility of arrhythmias, but inducibility did not predict clinical recurrence in follow‐up. Distinguishing organized atrial arrhythmias from AF did not yield any further prognostic information. The utility of aggressive stimulation protocols after AF ablation for prognosis and to guide therapy appears limited.